Correlation Of Ron95 And Ron97 Gasoline Properties From Various Brands Towards Engine Performance And Emission - Mohd Riduan, Aizuddin Fahmi (2020)
Effects of gasoline variations from different brands on vehicle performance have always been a debate among users and currently the facts remains inconclusive. Some claimed using a higher octane or particular fuel brand could affect overall engine behaviour, and when they do publically spread their own gathered findings, results collected were mostly done unscientifically. To overcome these problems, three objectives were planned for this research. Firstly, gasoline properties differences between Research Octane Number 95 (RON95) and RON97 from commonly available fuel brands in Malaysia were determined. Then, the examined gasoline properties were correlated towards engine performance and emissions through engine dynamometer testing. Lastly, influence magnitude of using different fuel brands and RONs towards overall engine behaviour were analysed. Research methodology was divided into Part A (Gasoline Properties Investigation) and Part B (Engine Testing Using Different Fuel Grades). In Part A, gasoline density, specific energy, and chemical formula group were determined utilizing a hydrometer, oxygen bomb calorimeter, and Fourier transform infrared spectrometer respectively. For Part B, an engine dynamometer and gas analyser were used to measure engine overall outcomes. Results gathered were torque, power, relative knock index, brake specific fuel consumption (BSFC), engine efficiency, carbon monoxide (CO), carbon dioxide (CO2), and nitrogen oxide (NOx). Gasoline density and specific energy results among each fuel samples demonstrated marginal differences, with biggest variation did not even exceeded 6%. Gasolines chemical content had presented all RON97 fuels possessed two additional chemical formula group which were polyetheramine and ethyl acetate. Every engine power and torque figures displayed minor variations of less than 4%. Nevertheless, relative knock index, BSFC, and engine efficiency did exhibited larger differences as certain cases depicted more than 10% deviation. Emission outputs were more substantially varied than all engine performance results, with CO and NOx shown variations of up to 20%. However, CO2 outcomes differed between tested fuels by just less than 4%. Gasoline specific energy was proven having direct connection towards engine torque and power. Fuel energy density was illustrated having an overall effect on engine knock. BSFC were deduced to be possibly influenced by gasoline energy content, whilst at the same time had significant effect on engine efficiency. Ethyl acetate presence in RON97 fuels was established directly correlated towards gas emissions, where it help produced lower CO and higher CO2 results than all RON95 gasolines. NOx emission was postulated to be linked with engine power since it could lead towards greater in-cylinder temperatures at higher outputs. Most engine outputs were better performed with RON97 fuels. However, with not even exceeding 2% engine performance improvements based on averaged results trend lines, employing a higher octane gasoline cannot be recommended since it is 15% pricier than RON95. Consumers can use collected finding as reference when comparing between fuels and no longer need to speculate because entire investigation was done in a controlled environment. Outcomes from this study could become a baseline for gasoline ma